Implementasi Kurikulum Merdeka Kelas III di SD Al-Munawarah Sentani (Kabupaten Jayapura) (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the implementation of the Independent Curriculum in third-grade students at Al-Munawarah Elementary School, Sentani, Jayapura Regency. Using a qualitative approach with data collection techniques through observation, interviews, and documentation, this study evaluated three main aspects: planning, implementation, and evaluation of learning. The results showed that during the planning stage, teachers developed teaching modules that referred to Learning Outcomes (CP) and prepared assessment instruments in the form of projects and prompt questions. During the implementation stage, teachers implemented an inquiry-based learning model to encourage student engagement and utilized various media, from printed books to digital devices, which positively impacted student engagement in class. During the evaluation stage, teachers used cultural project assessments and Student Worksheets (LKPD), accompanied by positive feedback to motivate students. Although implementation generally proceeded according to the curriculum framework, obstacles were still encountered in the application of differentiated learning because teachers tended to use lecture methods and generalize the abilities of all students. Therefore, continuous improvement is needed so that learning planning can be more aligned with the characteristics and individual needs of each student.